2015
DOI: 10.1371/journal.pmed.1001881
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Home-Based Counselling Strategy on Neonatal Care and Survival: A Cluster-Randomised Trial in Six Districts of Rural Southern Tanzania

Abstract: BackgroundWe report a cluster-randomised trial of a home-based counselling strategy, designed for large-scale implementation, in a population of 1.2 million people in rural southern Tanzania. We hypothesised that the strategy would improve neonatal survival by around 15%.Methods and FindingsIn 2010 we trained 824 female volunteers to make three home visits to women and their families during pregnancy and two visits to them in the first few days of the infant’s life in 65 wards, selected randomly from all 132 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 41 publications
4
68
0
Order By: Relevance
“…Except in one trial, 25 subsequent meta-analysis 9 , 10 included trials done in places where neonatal mortality was considerably lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except in one trial, 25 subsequent meta-analysis 9 , 10 included trials done in places where neonatal mortality was considerably lower.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported a decrease in neonatal mortality in both intervention and comparison groups, accompanied by increases in newborn care practices and health-service uptake, suggesting underlying trends that had a larger impact than the trial intervention itself 20 . Others reported a doubling of facility deliveries during the trial period that was possibly due in part to increased transportation and better communications in the area 9 . A third study suggested that a reduction in neonatal mortality in both intervention and control groups was likely related to improvements in the living environment in the slum areas, such as covering gutters and better sanitation and electricity supplies 21 .…”
Section: Discussionmentioning
confidence: 99%
“…4). It is not sufficient just to increase the number of institutional deliveries, resources must also be made available to maintain and improve the quality of perinatal care that the health centre or hospital can offer 40.…”
Section: Future Challengesmentioning
confidence: 99%
“…8 However, trials of home-based counselling conducted in a larger population and in programme settings 9,10 showed a smaller risk reduction for neonatal mortality (RR: 0.93; 95% CI: 0.85-1.01). 9 A review of seven trials of women's groups based on participatory learning and action cycles published in 2013 reported a 20% reduction in neonatal mortality (RR: 0.77; 95% CI: 0.65-0.90). 6 The evidence prompted WHO to recommend community mobilization with women's groups to improve maternal and neonatal health.…”
Section: Introductionmentioning
confidence: 99%